TERPENOIDS AND PHYTOSTEROLS ISOLATED FROM PLUMERIA RUBRA L., FORM ACUTIFOLIA (AIT) WOODSON AND ITS FUNGUS PARASITE COLESPORIUM PLUMERIAE - M, Resende, C.; S, Barreto A.; R., Pinto, P.; H. C, Nascimento C. C.; De, Vasconcelos, S. D. D.; A.C., Azevedo, L.; R. S., Stephens P.; I., Nogueira R.; P., Saranraj,; F., Diré G.; et al. (Asian Journal of Pharmaceutical Research and Development, 2018)
The hexane and ethyl acetate extracts of the leaves from Plumeria rubra L., form acutifolia (Ait) Woodson and the methanolic extract from the fungus Coleosporium plumeriae Pat. were analized by high resolution gas chromatography (HRGC) and by high resolution gas chromatography coupled to mass spectrometes (GC-MS). The identification of the chemical constituintes is these extracts has been made by the automatic comparison of the mass spectra obtained standards within the NBS, Wiley and Wiley 275T librarys supplied with the mass spectrometer and by analized of the principal fragmentations. Phytochemical studies of the hexane and ethyl acetate extracts of the leaves showed nine terpenoids (5-ergosten-3b-ol, 5,22-stigmastadien-3b-ol, 4-stigmasten-3-one, 5-stigmasten-3b-ol, 12-ursen-3b-ol, 12-oleanen-3b-ol, 12-oleanen-3-one-28-oic acid, ursolic acid and 3b-acetoxy-12-oleanen-28-oic acid). The compounds 5-ergosten-3b-ol, 4-stigmasten-3-one, 12-oleanen-3-one-28-oic acid, ursolic acid and 3b-acetoxy-12-oleanen-28-oic acid have been described for the first time from Plumeria rubra L., forma acutifolia (Ait) Woodson. From the methanolic extract of spores of the fungus Coleosporium plumeriae Pat were isolated 5-stigmasten-3b-ol, methyl esters of long chain fatty acids (C18:0, principally) and one aromatic compound, N-methyl toluenesulfonamide. No previous phytochemical studies of this fungus have been reported.